2023
DOI: 10.12968/vetn.2023.14.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in practice: Schwartz rounds and veterinary clinical ethics committees

Abstract: Structured approaches to emotional and moral distress, such as Schwartz rounds and clinical ethical committees, are common in human medicine, but less so in veterinary medicine. Although different in their goals, they are both ways to provide organisational structures that support moral resilience. It is possible that, by creating a sense of moral agency and community, these interventions could also help to mitigate moral distress in staff members. Veterinary nurses have an important role to play in developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Schwartz Rounds (Box 1) have been run within NHS settings since 2009 and more recently have been introduced by one of the authors (AM) into a veterinary practice setting (Martin 2024). They are well‐researched and a study by Maben and others (2018) showed that regular attendees of (human‐centred healthcare) Schwartz Rounds halved their psychological distress over an eight‐month period, and individual and organisational benefits were reported.…”
Section: Two Types Of Groups To Support Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartz Rounds (Box 1) have been run within NHS settings since 2009 and more recently have been introduced by one of the authors (AM) into a veterinary practice setting (Martin 2024). They are well‐researched and a study by Maben and others (2018) showed that regular attendees of (human‐centred healthcare) Schwartz Rounds halved their psychological distress over an eight‐month period, and individual and organisational benefits were reported.…”
Section: Two Types Of Groups To Support Staffmentioning
confidence: 99%
“…Martin (2024) has demonstrated through a pilot study that there may be benefits to veterinary healthcare teams. Schwartz Rounds are an evidence‐based group reflective space where all staff are invited to come together to reflect on the emotional and social impact of the work they do.…”
Section: Two Types Of Groups To Support Staffmentioning
confidence: 99%